Effect of Coleus forskohlii extract on cafeteria diet-induced obesity in rats - Shivaprasad, Hebbani Nagarajappa (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Obesity is a metabolic disorder that can lead to adverse metabolic effects on blood pressure, cholesterol, triglycerides and insulin resistance and also increases the risk of coronary heart disease, ischemic stroke and type 2 diabetes mellitus. This study was designed to determine the effect of Coleus forskohlii on obesity and associated metabolic changes in rats fed with cafeteria diet. OBJECTIVE: The aim of this study was to evaluate antiobesogenic and metabolic benefits of C. forskohlii in cafeteria diet induced obesity rat model. MATERIALS AND METHODS: Rats were randomly divided into five groups of six animals in each group and as follows: Normal pellet diet group; cafeteria diet group; cafeteria diet followed by 50 mg/kg/d Coleus forskohlii extract (CFE), 100 mg/kg/d CFE and 45 mg/kg/d orlistat groups, respectively. Indicators of obesity such as food intake, body weight and alteration in serum lipid profiles were studied. RESULTS: Feeding of cafeteria diet induced obesity in rats. Administration of CFE significantly halted increase in food intake and weight gain associated with cafeteria diet. Development of dyslipidemia was also significantly inhibited. CONCLUSION: The observed effects validate that supplementation of CFE with cafeteria diet could curb the appetite and mitigate the development of dyslipidemia.